Estrutura e dinâmica da comunidade de amebas testáceas planctônicas em planícies de inundação : a padrões temporais, ambientais e espaciais. - Arrieira, Rodrigo Leite (2016)
Understanding the factors that control the community structure, as well as the relative importance of environmental and spatial factors in structuring communities, has become a major focus of ecological researches in recent decades. The research area of this thesis is 72 lakes of four Brazilian floodplains: Amazonian, Araguaia, Pantanal, and Paraná. Although several studies in these floodplains, a representative part of the diversity of testate amoebae remains unknown in these ecosystems. In the first approach of this thesis, we analyse the structure of planktonic testate amoebae community and the influence of environmental variables on species diversity in two hydrological periods. The results indicate a remarkable variation in richness, diversity, and abundance in both hydrological periods, showing predominantly highest mean values of these attributes in drought period. Furthermore, the testate amoebae diversity is mainly related to environmental variables linked to the hydrometric level and environmental productivity. In the second approach, we verify how the temporal and spatial variations in environmental processes influence the planktonic testate amoeba metacommunities in floodplains. The results highlight that the hydrological periods have different relative importance in environmental and spatial processes. The species sorting model is predominant in drought, while neutral model in flood periods, except in Paraná floodplain. In this ecosystem, the construction of dams alters the influence of the environmental and spatial factors. In summary, the testate amoeba communities are structured by environmental factors in drought and at random in flood period, except when the ecosystem is affected by anthropic interference, as the case of Paraná River floodplain.